Analisis Kebangkrutan Bank Melalui Rentabilitas, Capital dan Bankometer: Studi Pada Bank Umum Indonesia dan Malaysia - Nova Novita; Andi Salahudin Akbar; Puti Dwi Handayani (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2016)
This study aimed to analyze the accuracy of the two component of RBBR model as model of evaluation for the bank’s health with Bankometer as bankruptcy prediction model. The sample used is public bank in Indonesia and Malaysia from year 2011 to 2014. Data is processed by using a fixed effect model. In this research is measured by rentanility and capital, while S-Score is used to measure Bankometer. The results of this study indicate that the Bankometer model can be use in bankruptcy predicting. This study finds that only liquidity, credit and capital have impact to the bankruptcy. Bankometer calculation also show that banks in Indonesia and Malaysia was far away from bankrupt or unhealthy condition.